Enhancer of zeste homolog 2 (EZH2) expression is an independent prognostic factor in renal cell carcinoma - Wagener, Nina; Macher-Göppinger, Stephan; Pritsch, Maria; Hüsing, Johannes; Hoppe-Seyler, Karin; Schirmacher, Peter; Pfitzenmaier, Jesco; Haferkamp, Axel; Hoppe-Seyler, Felix; Hohenfellner, Markus (BMC cancer, 2010)
The enhancer of zeste homolog 2 (EZH2) gene exerts oncogene-like activities and its (over)expression has been linked to several human malignancies. Here, we studied a possible association between EZH2 expression and prognosis in patients with renal cell carcinoma (RCC).
Gesehen am 27.09.2023